Peran manajemen strategi dalam meningkatkan daya saing perusahaan di era digital - Ramadhani, Nayla Salsabila (Maliki Interdisciplinary Journal, 2025)
In the era of rapidly evolving globalization and digitalization, companies face the challenge of adapting to dynamic business changes. Strategic management is key to guiding organizations towards sustainable competitiveness. The research method used a qualitative approach with literature review from various journals and scientific articles. The study results indicate that companies that consistently implement strategic management tend to have a sustainable competitive advantage, particularly through the use of digital technology and product innovation. Furthermore, this competitive advantage is found to be highly dependent on the innovation capacity and quality of human resources in internalizing the strategy across all operational lines. Thus, investment in talent development and an innovative culture is a key prerequisite within the strategic management framework in the contemporary era.